1990
DOI: 10.1111/j.1471-4159.1990.tb08827.x
|View full text |Cite
|
Sign up to set email alerts
|

Bovine Brain Coated Vesicles Contain Adenosine A1 Receptors. Presence of Adenylate Cyclase Coupled to the Receptor

Abstract: Clathrin-coated vesicles purified from bovine brain express adenosine A1 receptor binding activity. N6-Cyclohexyl[3H]adenosine [( 3H]CHA), an agonist for the A1 receptor, binds specifically to coated vesicles. High and low agonist affinity states of the receptor for the radioligand [3H]CHA with KD values of 0.18 and 4.4 nM, respectively, were detected. The high purity of coated vesicles was established by assays for biochemical markers and by electron microscopy. Binding competition experiments using agonists … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

3
13
0

Year Published

1990
1990
1995
1995

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 32 publications
(16 citation statements)
references
References 44 publications
3
13
0
Order By: Relevance
“…The similarity in the expression pattern of the common alpha and beta subunits of G-proteins in CV to the one typical of bovine brain demonstrates that CV play a role in the subcellular transport of these guanine nucleotide regulatory proteins. The results are also consistent with studies that showed the presence of adenylate cyclase activity in brain CV (3,5,6). These findings suggest that receptors and their transduction machinery are co-transported in CV during their export or internalization in neurons.…”
supporting
confidence: 81%
See 3 more Smart Citations
“…The similarity in the expression pattern of the common alpha and beta subunits of G-proteins in CV to the one typical of bovine brain demonstrates that CV play a role in the subcellular transport of these guanine nucleotide regulatory proteins. The results are also consistent with studies that showed the presence of adenylate cyclase activity in brain CV (3,5,6). These findings suggest that receptors and their transduction machinery are co-transported in CV during their export or internalization in neurons.…”
supporting
confidence: 81%
“…Some of these studies demonstrated the pres ence of receptors functionally coupled to adenylate cyclase, thus providing indirect evi dence for the presence of the transductory guanine nucleotide regulatory proteins (G-pro teins) in CV. The recent development and availability of antisera of designed specificity for the alpha and beta subunits of G-proteins permits their detection and characterization (5,(8)(9)(10)(11)(12)(13). Taking advantage of the analytical power of Western blots, we have aimed in this study to provide direct immunochemical evi dence for the presence of two of the main sub units of the heterotrimeric G protein com plexes in CV from bovine brain.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, muscarinic acetyl choline (3), opioid (4), a2 -adrenergic (5) and adenosine receptors (6) have been demon strated to be present in the coated vesicles. Some of the receptors in the coated vesicles are suggested to be associated with adenylate cyclase via guanine nucleotide regulatory pro teins (G-proteins) (3,6). No direct evidence, however, has been obtained for the presence of G-proteins in the vesicles.…”
mentioning
confidence: 99%